THE NEXUS BETWEEN GENERAL COGNITIVE ABILITY OF IMAMSHIP AND MASJID PERFORMANCE: A MEDIATING QUANTITATIVE PERSPECTIVE - Abdulhadi Alade Tihamiyu Eniafe; Dr. Adi Anuar bin Azmin @ Che Wan; Prof. Madya. Dr. Shuhairimi (Journal of Islamic, Social, Economics and Development, 2021)
This study aims to formulate the mediating effect of Islamic Ethical Administrative Practice (IEAP) on the nexus (relationship) between general cognitive ability (GCA) of Imamship (leadership in Islam) and Masjid performance (MP) of the Islamic community (Muslim Ummah) in Lagos State, Nigeria. This study is quantitative using a cross-sectional survey questionnaire, and statistical techniques to analyze the collected data with partial least square structural - equation modelling - version 3 (PLS-SEM-V3). The determinants of IEAP include four dimensions which are: (a) Competition, (b) Effort, (c) Morally Responsible Behaviour, and (d) Transparency. The GCA of Imamship factors are (a) Knowledge/Wisdom, (b) Truthfulness, (c) Responsibility/Trust, and (d) Deliverance of Khutbah. While the MP is measured with three dimensions: (a) Masjid Attendance, (b) Masjid Activities, and (c) Masjid Funding. The researcher sampled 310 Chief Imams of Central Masaajid (mosques) as respondents in Lagos State of Nigeria. The findings showed that all the IEAP factors had a significant positive relationship with GCA of Imamship and MP. The results of the study provide some insights into the Imamship of Masaajid in Lagos State, Nigeria in particular, and all other Masaajid in the country in general.